2021
DOI: 10.3889/oamjms.2021.6808
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Distribution of Pulmonary Tuberculosis in Kabanjahe District, Karo Regency, Indonesia

Abstract: BACKGROUND: Tuberculosis is an infectious disease and global concern today. AIM: This study aims to map the incidence of pulmonary tuberculosis risk factors in Kabanjahe District, Karo Regency. METHOD: This research is an ecological study with a case-control study design. This research was conducted in Kabanjahe District in January - October 2020. All people who checked and declared to have tuberculosis based on clinical symptoms to be the population in this study. The sample size was calculated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Because environmental factors and unsupportive income are the causes of pulmonary TB. In fact, nutritional problems are multicomplex because not only economic factors play a role but other factors also determine (Tanjung et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because environmental factors and unsupportive income are the causes of pulmonary TB. In fact, nutritional problems are multicomplex because not only economic factors play a role but other factors also determine (Tanjung et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Basically, intervention and policy programs are needed to tackle pulmonary TB which is prioritized on the characteristics of each region and pay attention to the most correlated risk factors in each region (Tanjung et al, 2021). Communication, resources and Standars Operating Procedure have an important role on the success of pulmonary TB control programs, especially in case detection of pulmonary TB patients (Syakbania & Wahyuningsih, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Another study in Indonesia found that the dominant factor in the incidence of tuberculosis is humidity. Houses that have ineligible humidity are at risk of developing tuberculosis by 3.1 times compared to houses that have sufficient humidity [12]. Another study in Semarang found that people living in homes with ineligible humidity are more at risk of contracting…”
Section: Resultsmentioning
confidence: 99%